Industry Self-Governance and National Security: On the Private Control of Dual Use Technologies - Sebastian von Engelhardt; Stephen Maurer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Private sector firms frequently sell dual use products that can be used to develop either civilian goods or weapons of mass destruction. The global character of these markets makes traditional regulation and treaty solutions difficult. Some existing initiatives by manufacturers have established private regulations that are stronger than official US policy. This paper explores the economic conditions that make such strong, industry-wide agreements stable. We assume two risks due to the dual use nature. First, upstream firms face legal liability if their products lead to a disaster. Second, a disaster may produce regulatory backlash, i.e. excessive government regulation that make downstream production prohibitive costly. We find that regulatory backlash is never an adequate substitute for perfect (i.e. full) liability and even makes the situation worse. Second, industry regulation enforced by downstream firms and optimal regulation converge when the downstream firms have strong market power. Next, we analyze when and why large downstream firms are able to force their preference for high levels of regulation on upstream suppliers. Finally we show that upstream incumbents may be able to deter entry in adopting a high regulatory standard.
Keywords: L51; L59; D82; 330